Strategies for Agile Leadership in a Challenging Environment - Blair, Garry; Barratt, Stuart; Pagano, Rosane (GS Spark: Journal of Applied Academic Discourse, 2023)
The post pandemic environment has provided many significant challenges for all forms of organisations. The requirement for good leadership in this context is vital. This research considers the features of such leadership and how their application can affect organisations and their required outputs. The need for agility in this sphere is proposed, in order to accommodate the environmental challenges, globally and within the different sectors. There should be an emphasis on creativity in order to provide solutions to the many issues for organisations in the prevailing environment. Recruitment and retention are viewed as critical activities for sustaining these entities by ensuring the supply of the requisite standard of personnel at all levels. The latter should have suitable qualifications or the aptitude to acquire them. These staff should be given appropriate training then empowered, including being given the scope to utilise their own leadership style, as appropriate. The form of the post pandemic environment and its effects on leadership are noted. The principal factors identified here include the economic challenges, hybrid working patterns and the use of agency staff to supplement the permanent resource. The proactive development of leaders is emphasised as a critical activity for organisations, enabling them to address the issues prevalent in their environment. Research into this area occurred, using qualitative techniques. A literature review and interview with a current practitioner were performed, in order to glean the data for an inductive analysis. A template to assist organisations in creating a strategy for ‘Agile Leadership’ was then formulated.